Predictive value of CA 19-9 in patients with pancreatic tumours: Predictive value of CA 19-9 in patients with pancreatic tumours (Journal of Fatima Jinnah Medical University, 2020)
Background: Pancreatic carcinoma is a disease with high modality and has a high incidence of recurrence after surgical resection. The prognosis depends on early diagnosis and treatment. Numerous international studies have reported use of CA 19-9 in diagnosis of pancreatic cancer. We planned this study to validate role of CA 19-9 in our local population. The objective of this study is to correlate raised serum CA 19-9 levels in patients with pancreatic tumours to distinguish between benign and malignant pancreatic disease.Subjects and methods: The present study is a validation study. Thirty-five patients with diagnosis of pancreatic tumor on radiological imaging were included after their informed consent. Data collection forms were filled, blood samples were taken and serum CA 19-9 was estimated by ELISA in Biochemistry department, SIMS. Histopathology samples were collected at time of surgical resection, sent to pathology departments of respective hospitals and histopathological reports collected. All data was collected and analysed by using descriptive method. The study was conducted in Biochemistry department of PGMI and SIMS, Lahore from May 2015 till June 2016.Results: Out of 35 patients, nineteen (54.3%) were female and sixteen (45.7%) were male. Thirty [85.7%] patients were between third to seventh decades of their life. The mean age range around 47.28. Thirty-four patients had malignant tumor and 1 benign on histopathology. CA 19-9 was raised (>37 U/ml) in 33 out of 34 patients with malignant pathology. The patient with benign pathology had CA 19-9 level
Keywords: Pancreatic tumour; CA 19-9; Sensitivity; Specificity